Pengaruh Bahan Organik dan Suhu Pengeringan terhadap Ketahanan Hidup Aspergillus niger dalam Pupuk Pelet Bio-fosfat - Yudi Sastro; Donny Widianto; Irfan D. Prijambada (Universitas Atma Jaya Yogyakarta, 2007)
This research was aimed to investigate the effect of organic matter and drying temperature on Aspergillus niger survivability in the rock phosphate pellet fertilizer namely bio-phosphate. The research was arranged by a completely randomized design 3x3x6. Addition of the mixing of tapioca waste, rice bran, and starch (BOC) and the humic substance (BH) in the bio-phosphate, and its drying temperature (SP) were the treatments. Aspergillus niger inoculums survivability in the bio-phosphate was determined using plating methods. The result showed that the addition of BOC decreased amount of A. niger in the bio-phosphate up to 28.0%, while the BH increased the amount of A. niger up to 24.4%. The ideal drying temperature of bio-phosphate pellet fertilizer was 600C.